The link between serum cotinine levels and gallstones prevalence in adults: a cross-sectional analysis using NHANES data (2017–2020) - Liu, Xin; Zhang, Zheng; Wang, Haoran; Faisal, Shah; He, Meng; Tai, Sheng; Lin, Yujia (Frontiers in Nutrition, 2024)
Background Gallstones represent a prevalent health issue globally, resulting in significant annual healthcare costs. While tobacco exposure is recognized for its association with numerous diseases, its correlation with gallstones remains contentious. Serum cotinine, a metabolite of nicotine, serves as a widely utilized indicator for assessing tobacco exposure. Crucially, no research has yet examined the association between serum cotinine levels and the gallstones. Methods This study is designed as a cross-sectional analysis, utilizing data from the NHANES public database. The relationship between serum cotinine levels and gallstones was analyzed using multinomial logistic regression models and smooth curve fitting. Subgroup analyses and interaction tests were performed to examine the potential contributions of different populations and covariates to the findings. Results A total of 5,856 participants were included in this study. After adjusting for relevant covariates, the multiple logistic regression model results indicated that for each unit increase in serum cotinine concentration above 0.29 ng/mL, there was a 29% increase in the prevalence of gallstones. Furthermore, smooth curve fitting analysis revealed a positive correlation between these variables. These findings underscore the impact of tobacco exposure on gallstone prevalence. Conclusion This study demonstrates a positive correlation between tobacco exposure, as measured by serum cotinine levels, and the prevalence of gallstones, thus adding to the body of existing research on this relationship.